Collective decision making in Euripides’ Supplices - Werner, Christian (Revista Archai, 2022)
In Supplices, one of Euripides' most political tragedies, a surprising approximation between the world of myth and that of the spectator is produced. AlthoughTheseus, its protagonist, is represented as a “democratic king”, it does not present a scene that can be compared to the experience of the most typical institution of Athenian democracy, the collective deliberation that defines the assembly open to all citizens. However, at different times in the first episode, it comes pretty close. Thus, the aim of this paper is to discuss how this tragedy represents forms of deliberation and consensus, and so it investigates the intricacies of two scenarios that lead toan attack war policy developed in the drama, one in Argos, the other in Athens.